Optimization of machining parameters using taguchi coupled grey relational approach while turning inconel 625 / Chinmaya Padhy and Pariniti Singh - Padhy, Chinmaya; Singh, Pariniti (Universiti Teknologi MARA, 2021)
In manufacturing industries preparation of quality surfaces is very important. The surface roughness will influence the quality and effectiveness of the subsequent coatings for protection against corrosion, wear resistance etc. For achieving desired surface roughness, factors like cutting force (N) and material removal rate (mm3 /sec) plays an important role towards final product optimization. This study helps to determine the contribution of each machining parameters [cutting speed (v), feed rate (f) and depth-of-cut (d)] and their interaction to investigate their optimum values during dry turning of Inconel 625 with the objective of enhancing the productivity (optimum production) by minimizing surface roughness (Ra), cutting forces (Fc), whereas maximizing material removal rate (MRR). This kind of multi response process variable (MRP) problems usually known as multi-objective optimizations (MOOs) are resolved with the help of Taguchi and Grey relation approach (T-GRA). As a result, the attained optimum cutting parameters are viz. cutting speed (60 m/min), feed rate (0.3 mm/rev), depth-of-cut (0.25 mm) lead to value of desired variables - cutting forces (340 N), surface roughness (0.998 μm) and material removal rate (0.786 mm3 /min).